Shoulder dominant maximum strength and speed power of amateur boxers - Tasiopoulos, I.; Tripolitsioti, A.; Skordis, D.; Stergioulas, A. (22nd International congress of physical education & sport, Komotini, Greece, 2014)
Boxing depends on these forms of strength in varying degrees, something reflected in the requirements of the sport. The force measurements represent specific quality parameters indicative of the neuromuscular function and its assessment considers the level of the variables that affect the production of skeletal muscle The purpose of this study was to determine the maximum strength at 60°/sec and the speed power at 180o/sec of internal and external rotators of shoulder in amateur boxing athletes and compare them with the years of engaging in the sport. Thirty five volunteer boxing athletes took part in this study, aged 24.52 ± 4.85 years, stature 1.74 ± 6.42 cm and body weight 76.52 ± 11.1 kg. The determination of the maximum strength and power of an amateur boxer was made with the help of the Kin-Com dynamometer through standard procedures. The motion in internal rotator was from the 90o to 0 degrees and vice versa in the external rotator from 0o to 90o degrees. It was assumed that there will be significant differences between maximal strength and power of boxers with years of engagement in the sport. The analysis of variance (ANOVA) was used for the analysis of parameters of this study. After processing the data the following statistically significant differences were obtained: a ) Between power (180o/sec ) of internal rotation of the dominant limb during concentric contraction and the boxers` years of involvement with the sport (F = 3.102, p <0.05), b ) Between power (180o/sec ) of external rotation of the dominant limb during eccentric contraction and the years of involvement in the sport (F = 4.139, p <0.028), c) between maximal strength (60° / sec) of external rotators of the dominant limb during concentric contraction and years of involvement in the sport (F = 5.070, p <0.014) and d) between maximal strength (60° / sec) of external rotators of the dominant limb during eccentric contraction and years of involvement in the sport (F = 4.300, p <0.024). Further analysis by the method bonferroni revealed the following significant differences : 1). Among power (180o/sec ) of internal rotators of the dominant limb during concentric contraction of the boxers who had been boxing over 10 years and those who trained in the last five years (p <0.05), 2). Among power (180o/sec ) of external rotators of the dominant limb during eccentric contraction of the boxers who had been boxing over 10 years and those who trained in the last five years (p <0.013), 3). Between maximal strength (60o/sec ) of external rotators of the dominant limb during concentric contraction of the boxers who had been boxing over 10 years and those who trained in the last five years (p <0.021), 4). Between maximal strength (60o/sec ) of external rotators of the dominant limb during eccentric contraction , the boxers who had been boxing over 10 years and those who trained in the last five years (p <0.024). The results of the study confirmed the hypothesis that there will be significant differences between maximal strength and power with the years of involvement in boxing. It is concluded that both the maximal strength and the speed power of amateur boxing athletes in the reported angular velocities seems to improve with the years of training.